In Search of Consistency in International Law on the Right to Self-Determination, Non-Interference, and Territorial Integrity - Okeke, Charles (Technium Social Sciences Journal, 2022)
The right to self-determination and its complexity in relation to non-intervention and territorial integrity continue to be the subject of numerous academic inquiries. Governments have recently encountered public demands for this right, and the people occasionally experience repression to stifle their voices. International groups that monitor and record abuses of various human rights have sparked interventions because to a post-cold war focus in defending collective rights. It is still true today that the promotion of the right to self-determination has given rise to international practices that have significantly impacted and clashed with the principle of non-interference. This paper focuses on the consistency or lack of in international law on the right of self-determination, the principle of non-interference, and the contemporary legal trend to promote the rights of all peoples within breaching the principle of territorial integrity. While tracing the relevant legal shifts in both international legal and political practices and in emerging doctrines and principles in international law, this study provides ideas to the discussion of the concept of non-interference. International law prohibits the use of force against an independent state; the only exception is where there is a flagrant violation of human rights and a credible threat to international peace and security. As a result, force can only be used as a last resort if all other efforts to reach a peaceful settlement have failed.